An examination of differences in financial performance among age cohorts - Weeden, Gabriel T. (Kansas State University, 2008)
The overall objective of this study was to examine the relative efficiency of farmers in various age groups. Nine Hundred sixty-four sole proprietors, who were members of the Kansas Farm Management Association (KFMA) with continuous data from 2002-2006, were split up into four groups based on age. Comparing the fourth age group (over 65 years of age) to the first age group (under or equal to 45 years of age) was of primary importance in this study. Comparisons were made utilizing variables pertaining to farm size and tenure, specialization, efficiency, liquidity, and solvency. In this study, there are four age groups; under or equal to 45 years, 46 to 55 years, 56 to 65 years, and greater than 65 years old. T-tests were used to compare variables among age groups. Nineteen variables were statistically different between age groups one and four. The fourth age group performed poorly in terms of cost efficiency. Based on the results, the fourth age group had a difficult time covering unpaid labor and capital expenses. Discriminant analysis was used to determine which variables discriminate the most between age groups. The top three variables in this discriminant analysis were the asset turnover ratio, the economic total expense ratio, and percent acres owned. The top three variables in the discriminant analysis involving groups one and four were the debt to asset ratio, asset turnover ratio, and net farm income.
Keywords: Kansas farmer efficiency; Efficiency based on age; Financial performance among age cohorts; Sole proprietors; Economics, Agricultural (0503)